Trade Liberalization and Human Capital Accumulation: Evidence from Indian Census - Mehtabul Azam (Institute of Labor Economics (IZA), 2022)
We exploit the pre-reform employment composition of Indian districts and differential tariff cuts across industries introduced by the 1991 trade liberalization to examine the impact of liberalization on human capital accumulation measured by completion of different stages of schooling and aggregate schooling. Using Census 2011 data, we divide age cohorts that attended school before and after liberalization to implement cohort wise difference-in-difference strategy. We also construct a district-level panel using four decennial censuses that covers 1981-2011 and get an alternative difference-in-difference estimate by looking at the pre and post liberalization outcomes. We find that once we allow for the differential state policies, there is no evidence that the Indian trade liberalization has any impact on either aggregate schooling or on the attainment at different stages of schooling. We find suggestive evidence that positive effect of the increased returns to education was mitigated by the increased opportunity cost of schooling.
Keywords: O15; O19; J24; F16; F63; 330; liberalization; human capital accumulation; difference-in-difference